Activity of chitosan-montmorillonite bionanocomposites incorporated with rosemary essential oil: From in vitro assays to application in fresh poultry meat. (April 2019) - Souza, Victor Gomes Lauriano; Pires, João R.A.; Vieira, Érica Torrico; Coelhoso, Isabel M.; Duarte, Maria Paula; Fernando, Ana Luisa
Abstract: The aim of this work was to develop bionanocomposites based on chitosan/montmorillonite (MMT) incorporated with rosemary essential oil (REO) and to evaluate its activity as primary packaging of fresh poultry meat. Chitosan film form dispersions were incorporated with MMT and different levels of REO (0.5%, 1% and 2% v/v). Good interaction between the phenolic compounds present in the REO, the MMT and the chitosan was observed from FTIR spectra. The incorporation of REO increases film permeability to both water vapour and oxygen, whereas MMT incorporation reduced both permeabilities. However, all the developed films showed oxygen permeability values comparable with EVOH (a gas barrier used in packaging). In the in vitro essays, chitosan films with REO demonstrated good antimicrobial activity against Bacillus cereus (reduction of 7.2 log) and Salmonella enterica (reduction of 5.3 log) and in the migration assay, the total phenolic compounds increased with the level of REO incorporated. In the in situ essays, fresh poultry meat was wrapped with the films developed and stored under refrigeration (5 °C ± 2 °C) for 15 days. Compared to control (meat without film), meat wrapped with bioplastics showed reduction of 1.2–2.1 log CFU/g on the total microorganisms count, and active films also succeeded on retarding poultry lipid peroxidation and discoloration. Yet, the incorporation of MMT increased the interaction between the polymer/phenolic compounds/MMT, diminishing the release of the active compounds. In conclusion, the films showed potential to be used by the food industry, once they can substitute the commercial plastic films and extend products (poultry meat) shelf life. When improvement of the mechanical properties is not an issue, chitosan incorporated with REO and without MMT are the most promising materials. Graphical abstract: Highlights: Essential oil plasticizes the chitosan increasing oxygen and water vapor permeabilities. Natural montmorillonites retard the migration of phenolic compounds from chitosan matrix. Active films were efficient in the shelf life extension of poultry meat.